MODEL PEMBERDAYAAN REMAJA MELALUI PELATIHAN PENCEGAHAN STUNTING BAGI CALON PASANGAN SUAMI ISTRI: (STUDI RISET & PENGEMBANGAN DI WILAYAH BOGOR) - Wahyudi, Udi; Wahyudin, Uyu; Suryadi, Ace; Sudiapermana, Elih (Poltekkes Kemenkes Bandung, 2024)
Stunting is a global health problem affecting many countries, including Indonesia, with serious long-term impacts on children's growth and development. This phenomenon requires special attention because it can affect the quality of life and future potential of individuals. This study aimed to design a relevant and effective adolescent empowerment model to prevent stunting, focusing on prospective married couples in the Bogor area. The research method used is the 4-D model development design (Four D Models), which includes four main stages: Define (problem determination), Design (model design), Develop (model development), and Disseminate (model dissemination). The results of this study indicate that prospective married couples in Bogor have very limited initial understanding of how to prevent stunting. This finding highlights the need for active involvement of adolescents in the education process and decision-making related to stunting prevention. In addition, community support has proven to be very important in changing behavior and raising awareness about stunting. This study also underlines the importance of a solid monitoring and evaluation system to ensure that the empowerment model developed can be implemented sustainably and effectively. By implementing the empowerment model widely and continuously monitoring its implementation, it is hoped that it can optimize stunting prevention efforts in the future and have a positive impact on public health in the Bogor area.